First description of the adult male of Epeorus aculeatus Braasch (Ephemeroptera: Heptageniidae) - Webb, J. M.; Mccafferty, W. P. (Zootaxa, 2006)
The male imago of the southeast Asian species Epeorus aculeatus Braasch is described for the first time, based on reared material from Thailand.